Senggol market development strategy as a culinary tourism attraction in the city of Gianyar, Bali - Francisca Titing Koerniawaty; I Made Sudjana; Putu Eni Oktaviani (Institute of Computer Science (IOCS), 2022)
This study aims to determine the potential and strategy for developing Senggol Market as a culinary tourism attraction in Gianyar City, Bali. Data analysis used in this research is internal factor analysis using IFAS, external factor analysis using EFAS, and SWOT analysis. The results of the study show that the strategy that can be designed is the Growth (development) strategy with the main strategy of fulfilling the 12 indicators of culinary tourism attractiveness for Senggol Market first so that it is worthy of being said as a culinary tourism attraction, after that then intensify promotions and attract investors. Data analysis used in this research is internal factor analysis using IFAS, external factor analysis using EFAS, and SWOT analysis. The results of the study show that the strategy that can be designed is the Growth (development) strategy with the main strategy of fulfilling the 12 indicators of culinary tourism attractiveness for Senggol Market first so that it is worthy of being said as a culinary tourism attraction, after that then intensify promotions and attract investors. Data analysis used in this research is internal factor analysis using IFAS, external factor analysis using EFAS, and SWOT analysis. The results of the study show that the strategy that can be designed is the Growth (development) strategy with the main strategy of fulfilling the 12 indicators of culinary tourism attractiveness for Senggol Market first so that it is worthy of being said as a culinary tourism attraction, after that then intensify promotions and attract investors.